Novel Hybrid Orthogonal Large Set Code Sequence for High Density Wireless Networks - Nyoman Pramaita; P. L. Johnson (Institut Teknologi Sepuluh Nopember, 2014)
CDMA technique has been successfully employed to implement high capacity mobile networks with optimum channel bandwidth utilization. The two most coveted criteria for the spreading codes used in such network are, the number of codes in the set and the code orthogonality, in order to ensure accommodation of large number of users and as well as minimal interference between the users. Walsh code has proved to be a popular orthogonal code, whereas m-sequence, Gold code and Kasami code have established themselves as popular non-orthogonal binary codes. Small set Orthogonal Kasami code has been proposed and evaluated by researchers for CDMA applications. In this paper the authors report the design of hybrid orthogonal large set (HOLS) code for synchronous CDMA systems. The HOLS code was evaluated in a synchronous CDMA system over different channel conditions. The authors also demonstrate that the BER performance of the HOLS code is comparable to that of the existing orthogonal codes, but outperforms Gold and large set Kasami code sequences. The HOLS code sequence is also shown to outperform the existing code sequences in the number of cells it can support. In terms of multiple access interference (MAI), the cross-correlation function (CCF) of the HOLS code sequence is comparable to that of Walsh and orthogonal small set Kasami codes, and much better than those of Gold and large set Kasami code sequences. HOLS code sequence has comparable auto-correlation function (ACF) with that of Gold, large set Kasami and orthogonal small set Kasami code sequences and a much better ACF than that of Walsh code sequence.